The effect of work-related ICT use outside work hours on work-family balance: Mediating roles of work-family conflict and work-family enrichment among non-academic staff in public universities in Malaysia - Azimah Ahmad (2024)
Challenges in balancing work and family often arise from increased work demands that interfere with personal life. In the 21st century, workplaces have transformed significantly, with technology allowing employees to use ICT for work-related tasks even outside of regular working hours. The modern workplace is becoming more flexible and engaged as companies increasingly rely on mobile technology to perform work tasks among employees. This trend has blurred the line between work and employees’ family time, as employees may feel compelled to carry out the work, even without written contractual obligations. While there is a growing number of work-related ICT uses outside work hours and premises, the impact of technology on individuals and families is inconclusive. The purpose of this study was to examine the moderated mediation between work-related ICT use outside work hours and work-family balance, considering work- family conflict and work-family enrichment as a mediator and the effects of integration preference, organisational integration norms, and ICT demand as the moderator. A quantitative research approach was employed through a questionnaire survey involving 665 respondents who are non-academic employees of public higher education institutions in Malaysia. Analysis of Moment Structures (AMOS) and Statistical Package for the Social Sciences (SPSS) were used to complete the data analysis. This study's outcome showed a positive effect between work-related ICT use outside work hours and work- family balance. Also, work-family conflict and work-family enrichment showed mediating effects between work-related ICT use outside work hours and work-family balance. Furthermore, the results revealed that integration preference, organisational integration norms, and ICT demand significantly moderated the relationship between work-related ICT use outside work hours on work-family conflict and work-family enrichment. The majority of non-academic employees perceive their work-family balance to be reasonable despite frequently engaging in work-related ICT use outside work hours. Hence, the impact of staying connected to work outside of work hours may help reduce work-family conflict and improve work-family balance. The study’s limitations and its focus on higher education institutions may limit the generalisability of the findings to other sectors. The results of this study may help governing bodies, especially in public universities, or enhance relevant policies to support sustainable work-family balance practices within their educational institutions.